Barthez entre Montpellier e Paris: a complexa rede por trás da ciência do homem - Amaral, Maria Thereza Cera Galvão do (2010)
This paper presents the dynamics of the physiological system of Paul-Joseph Barthez and where this system was inserted, done through a review of the book Nouveaux Éléments de la Science de l'Homme ". Physician, physiologist, scholar, professor and head of the Medical University of Montpellier, France, was born in Montpellier and exercised their professional activities in Montpellier and Paris in the eighteenth century